?DISSOLUTION OF PHOSPHORITE IN DILUTE HYDROCHLORIC ACID SOLUTION (Biological Sciences - PJSIR, 1994)
A powdered phosphorite ore was leached in dilute solutions (0.14 -3.15 mol 1.1) of hydrochloric acid at tempera- ture ranging from 50 to 70". Both phosphorus and calcium were extracted in a nearly stoichiometric ratio. The rate of extraction of both elements was controlled by diffusion ofthe reagent through aresidual layer of non-soluble components of the phosphorite, and not by surface chemical reaction. The apparent activation energies were evaluated for both elements and results given.